2013
DOI: 10.1038/msb.2012.67
|View full text |Cite
|
Sign up to set email alerts
|

Widespread splicing changes in human brain development and aging

Abstract: Human brain transcriptome analysis revealed widespread age-related splicing changes in the prefrontal cortex and cerebellum. While most of the splicing changes take place in development, approximately one-third of them extends into aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
198
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(207 citation statements)
references
References 52 publications
(74 reference statements)
9
198
0
Order By: Relevance
“…It is currently unclear to what extent the transcriptional changes that occur during aging or/and senescence in mammals are a consequence of histone reduction. However, and interestingly, intron retentions are the most abundant age-related splicing changes found in the human brain (48). Therefore, our results prompt us to hypothesize that the splicing alterations found during human aging might be caused by the associated histone depletion.…”
Section: Discussionmentioning
confidence: 82%
“…It is currently unclear to what extent the transcriptional changes that occur during aging or/and senescence in mammals are a consequence of histone reduction. However, and interestingly, intron retentions are the most abundant age-related splicing changes found in the human brain (48). Therefore, our results prompt us to hypothesize that the splicing alterations found during human aging might be caused by the associated histone depletion.…”
Section: Discussionmentioning
confidence: 82%
“…This trend is evident in both wild‐type mice during physiological aging and in a premature aging mouse model, suggesting that alternative splicing might be more important in the aging process than has previously been noted. Our results are in agreement with those of other recent studies that have shown an effect of age on AS in human brain (Tollervey et al ., 2011; Mazin et al ., 2013), human peripheral blood leukocytes (Harries et al ., 2011), and senescent fibroblasts induced by telomere shortening (Cao et al ., 2011). To our knowledge, this is the first study to show that the amount of age‐related AS increases with more advanced age (4–18 months compared to 4–28 months) and in several tissues.…”
Section: Discussionmentioning
confidence: 99%
“…This result can be compared to that of the Mazin et al . 's (2013) study in human brain using high‐throughput sequencing, which found that nearly 40% of the genes expressed in human brain had changes in splicing over postnatal life. Of these, 70% occurred during development and 30% during aging, and 12% of the total number of genes expressed in the brain had aging‐related splicing (Mazin et al ., 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many splicing factors show age‐related changes in their expression that correlate with changes in alternative splicing during aging (Harries et al, 2011; Lee et al, 2016; Mazin et al, 2013; Rodríguez et al, 2016; Tollervey et al, 2011; Wood, Craig, Li, Merry, & Magalhães, 2013). For example, as many as one‐third of all splicing factors exhibit altered expression with age in human blood (Holly et al, 2013).…”
Section: Introductionmentioning
confidence: 99%